ANTIOXIDANTS CONSUMPTION BY FEMININE ADULT HURDLER ATHLETES, IN THE 400 METERS COMPETITION WITH BARRIERS IN ATHLETICS MODALITY (Fiep Bulletin - online, 2011)
Being the best in what you do and reaching the highest spot in the podium is a goal for any athlete. And the feeding consists in an essential component for this ideal. Accordingly to this, it aimed to analyze, if the consumption of antioxidants food sources realized by athletes from the feminine adult category, in the 400 meters competition with barriers is appropriate. Because it is questioned that this population's diet doesn't provides properly such sources. Therefore, it applied the questionnaire method containing closed questions referring to personal data, knowledge level and feeding frequency. The results obtained showed that among the four raised questions, referring to the knowledge level, three had bigger percentage in the "just enough" knowledge option about the subject. About the feeding frequency, only one, of the five groups of antioxidants analyzed, was adequate to the daily consumption of antioxidants food sources. Evidencing that way, that the athletes fall short as to the intake of antioxidants food sources, what ends up contributing to the emergence of serious damage to medium-long term in their performance.
Keywords: Sportive nutrition; free radicals; feeding frequency